Proliferative kidney disease in rainbow trout (Oncorhynchus mykiss) under intensive breeding conditions: Pathogenesis and haematological and immune parameters - Palikova, Miroslava; Papezikova, Ivana; Markova, Zdenka; Navratil, Stanislav; Mares, Jan; Mares, Lukas; Vojtek, Libor; Hyrsl, Pavel; Jelinkova, Eva; Schmidt-Posthaus, Heike (Veterinary parasitology, 2017)
Proliferative kidney disease (PKD) is an endoparasitic disease of salmonid fish caused by Tetracapsuloides bryosalmonae (Myxozoa: Malacosporea). This study presents a comprehensive view on PKD development in rainbow trout (Oncorhynchus mykiss) reared at an intensive fish breeding facility, with focus on mortality, pathology/histopathology, haematological findings and immune functions. Diseased and reference fish were sampled monthly and time course of natural infection was followed up from the onset of clinical signs (September 2014) to full recovery (January 2015). PKD- associated cumulative mortality was 30% with a peak value in October, while immunohistochemical testing indicated a continuous significant decrease in T. bryosalmonae numbers from September to December; with no parasites detected in January. During peak clinical infection, a significant decrease in red blood cell counts, haematocrit values, haemoglobin concentration, along with a reduction in lymphocytes and a significant phagocyte elevation corresponding with an increase in phagocyte oxidative burst were measured in comparison to control animals. Complement activity and total immunoglobulin plasma concentrations were also elevated, though only during the initial monitoring period (September). Individuals surviving PKD, recovered and were able to fully regenerate both renal structure and haematopoietic parameters to normal levels. Changes in the red blood cell parameters indicate anaemia and a decreased oxygen transportation capacity during the clinical disease phase. Together with an increased oxygen demand at higher temperatures and decreased oxygen solubility this could lead to decompensation and elevated mortality. The stimulation of immune parameters, and especially oxidative phagocytic burst, is likely to have had a strong effect on both, regeneration and elimination of the pathogenic agent.
Keywords: teplota; Aquaculture; Disease Outbreaks; Disease Susceptibility; Temperature; Oxidative burst; Parasitic Diseases, Animal; Complement activity; Kidney Diseases; Oncorhynchus mykiss; Histology; vodní hospodářství; nemoci ryb; Animals; zvířata; náchylnost k nemoci; nemoci ledvin; Immunohistochemistry; epidemický výskyt choroby; Rainbow trout; Total immunoglobulins; Proliferative kidney disease; Fish Diseases; Myxozoa; parazitární nemoci u zvířat